Revolusi Industri, Teori Taylor, dan Teori Fayol - Wardatul Janah; Reindo Febrianto; Hendra Saputra; Asiyah Asiyah (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
The Industrial Revolution marked a significant milestone in the transformation of the workplace, creating a need for efficiency and more systematic structures within organizations. This development led to the emergence of various management theories, including Frederick W. Taylor's scientific management theory and Henri Fayol's general administrative theory. This study aims to examine the relationship between the changes brought about by the Industrial Revolution and the emergence of these two theories, as well as to examine their relevance and application in the context of modern management. The method used was a descriptive qualitative literature review, reviewing various classical and contemporary literature covering three main topics. The results indicate that Taylor's theory emphasizes work efficiency through standardization and scientific supervision, while Fayol's theory highlights the importance of managerial functions and structured organizational principles. Both responded to managerial challenges during the Industrial Revolution and remain relevant today, particularly in human resource management and organizational structure. The implications of this study demonstrate the need for a historical understanding of classical management theories in order to adapt these principles to address managerial challenges in the digital era and Industry 4.0.